Friends, family, and boyfriends: An analysis of relationship pathways into commercial sexual exploitation. (April 2019) - Reed, Shon M.; Kennedy, M. Alexis; Decker, Michele R.; Cimino, Andrea N.
Abstract: Background: The commercial sexual exploitation of children (CSEC) is a major global issue that affects over two million children each year (Polaris Project, 2014). Large metropolitan cities, such as Las Vegas, have high rates of child prostitution (Shared Hope International, 2009). Objective: The purpose of the current study is to elucidate to what extent interpersonal relationships and contextual factors (e.g. abuse within the home, substance abuse, etc.) influence commercial sexual exploitation. Participants and setting: Participants for this study include 26 CSEC survivors located within the state of Nevada. Methods: The current study utilizes a qualitative content analysis approach to analyze interview transcripts gathered from CSEC survivors. Three stages of analysis were conducted to assess the relationships that influenced the participants' sexual exploitation, as well as the contextual factors shared by the participants. Results: Analyses indicated that three types of relationships led to commercial sexual exploitation: friends, family, and boyfriends. Of the three relationship typologies, friends were the most common (n = 14). As for contextual factors, it was common for participants to have been abused within their home (n = 15) or to have run away from home (n = 20). Conclusions: The narratives provided in this study show that CSEC survivors do not often willingly engage in trading sex; rather this decision is influenced by a need to escape familial abuse or they are forced to trade sex by someone whom they share a relationship.